Psychosocial adjustment and depressed mood in teenagers in schools of Lima Metropolitana - Bulnes B., Mario S. (2005)
From the preoccupation by the increase of the depression frequency and the diminution of the age of the people who suffer this type of problem, as well as some indicators that accompanies it and that is within the concept of psycho-social misalignment, arise the necessity to study these phenomena in the scholastic population. Objectives: demostrate the interdependent relation of the variable adjustment psycho-social and depression in students of the city of Lima, Peru, in function to the type of school (state and private) and sort. Design: Descriptive comparative and correlational. Materials and methods: The sample was constituted by 480 students of state and particular educative centers, whose ages oscillate between the 12 and 17 years. For the evaluation of the variable psychosocial adjustment, the Inventory of Adaptation of Conduct of M. Victoria de la Cruz and Agustín Cordero was used, and to evaluate the variable depression, it was used the Questionnaire of Depression for children and adolescents of M. Lang and M. Tisher. The statistical analysis derived in the first place, in an analysis of validity and trustworthiness of the tests, and secondly, a inferencial analysis for the contrast of the raised hypotheses was made. Results: One has been that the two used tests are highly valid and reliable.